Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/horticulturae8020129
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Chemical Analyses Reveal the Hub Regulators of Flower Color Variation from Camellia japonica Bud Sport

Abstract: Camellia japonica is a woody ornamental plant with multiple flower color variations caused by bud sport; however, the molecular mechanism remains unclear. Here, chemical and transcriptomic analyses of C. japonica were performed with white, pink, red, and dark red flowers caused by bud sport. Seven anthocyanins were detected in these samples, except in C. japonica ’YuDan’ (white petals). The total anthocyanin content of C. japonica ’JinBiHuiHuang’ was the highest, and cyanidin 3-O-β-glucoside (Cy3G) was the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…DT and HA obtained the lowest TAC with no statistical differences (<24 g cyanidin-3-glycoside/g sample), which corresponds to pink blush flowers. According to Fan, TAC of C. japonica of different ecotypes ranged from 3.83 to 149.34 mg anthocyanin/100 mg [96]. Similar results were reported by Xiaowei, with an average content of anthocyanins of 0.828 mg anthocyanin/g sample [97].…”
Section: Evaluation Of Camellia As a Promising Source Of Bioactive Co...supporting
confidence: 77%
“…DT and HA obtained the lowest TAC with no statistical differences (<24 g cyanidin-3-glycoside/g sample), which corresponds to pink blush flowers. According to Fan, TAC of C. japonica of different ecotypes ranged from 3.83 to 149.34 mg anthocyanin/100 mg [96]. Similar results were reported by Xiaowei, with an average content of anthocyanins of 0.828 mg anthocyanin/g sample [97].…”
Section: Evaluation Of Camellia As a Promising Source Of Bioactive Co...supporting
confidence: 77%
“…Previous findings confirmed that GATA TFs may be directly or indirectly involved in anthocyanin biosynthesis ( Zhou et al., 2020 ; Fu et al., 2021 ; Wang et al., 2021 ; Fan et al., 2022 ; Zhou et al., 2022 ). Cho et al.…”
Section: Discussionsupporting
confidence: 56%
“…(2021) screened 19 key TFs involved in anthocyanin accumulation from five Camellia japonica cultivars with different petal colors using RNA-seq, including one GATA transcription factor that positively regulated target gene expression. Fan et al. (2022) cloned candidate genes related to anthocyanin synthesis from Camellia japonica and identified GATA binding sites in their promoter regions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the petal pigments in camellias are mainly derived from anthocyanins, with the red color being mainly from anthocyanins of the cyanidin glycosides [ 9 ], while the yellow pigment is mainly from the quercetin glycosides [ 8 ]. Although there have been some studies on the genes regulating petal flower color in different ornamental camellias [ 10 ], little is known about the molecular mechanisms underlying floral color domestication.
Fig.
…”
Section: Introductionmentioning
confidence: 99%